Studies on the performance of some garlic genotypes (Allium sativum L.) under subtropical conditions of Himachal Pradesh - K Jarial, D Sharma, S K Banyal, (Journal of Spices and Aromatic Crops, 2015)
Twenty six genotypes of garlic collected from commercial garlic growing pockets of Himachal Pradesh were evaluated for two consecutive years. Observations were recorded on various horticultural traits. The analysis of data revealed that the germplasm differed significantly for morphological attributes, yield and storage performance. The height of the plants varied from 39.70 cm to 76.71 cm. Length and width of the individual bulb ranged from 3.69 cm to 4.96 cm and 4.00 cm to 5.33 cm, respectively. The number of cloves/bulb and individual bulb weight also varied significantly. Per hectare yield of garlic genotypes varied from 0.92 t ha-1 to 2.60 t ha-1, lowest yield was recorded in NG-12 and highest in Agrifound Parvati. NG-25 had minimum storage loss (5.79%) after three months of storage. Considering yield and other parameters, the lines NG-1, NG-11, NG-25 and Agrifound Parvati were found promising.